2020
DOI: 10.1590/1516-4446-2019-0654
|View full text |Cite
|
Sign up to set email alerts
|

Mild and moderate cognitive impairment and mortality among Brazilian older adults in long-term follow-up: The Bambui Health Aging Study

Abstract: Objective: To compare mortality in older adults with and without mild or moderate cognitive impairment over 15 years of follow-up in a middle-income country, where little information on this subject is available. Methods: A total of 1,281 community-dwelling older adults were followed-up for a median of 13.3 years. We evaluated their cognitive impairment using the Mini-Mental State Examination, categorizing it as none (1.0 SD above cutoff means), mild (1.0 SD below cutof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Congruently with the above finding, observing the few studies published in the field over the years in Brazil, it is possible to notice a higher prevalence of cognitive impairment for adults over 60 years of age in more recent studies. For instance, the prevalence rate in samples collected until 2000 was between 11.5 and 19.2% [12][13][14][15], while the studies conducted in 2008 [16] and 2011 [17] showed a prevalence of 34.1 and 38.9%, respectively. For this reason, it is critical to identify the trends in cognitive impairment of representative samples across the years to explore the main protective and risk factors to its development, and as a result to provide effective training for health professionals, strategically allocate investments of governments [18], and develop populational health policies [19].…”
Section: Introductionmentioning
confidence: 96%
“…Congruently with the above finding, observing the few studies published in the field over the years in Brazil, it is possible to notice a higher prevalence of cognitive impairment for adults over 60 years of age in more recent studies. For instance, the prevalence rate in samples collected until 2000 was between 11.5 and 19.2% [12][13][14][15], while the studies conducted in 2008 [16] and 2011 [17] showed a prevalence of 34.1 and 38.9%, respectively. For this reason, it is critical to identify the trends in cognitive impairment of representative samples across the years to explore the main protective and risk factors to its development, and as a result to provide effective training for health professionals, strategically allocate investments of governments [18], and develop populational health policies [19].…”
Section: Introductionmentioning
confidence: 96%
“…To identify cognitive impairment using cut points of 23 or less or 24 or less), the MMSE has a sensitivity of 85 to 92% and a specificity of 85 to 93% [4]. Substantial researches have determined the association between cognitive impairment defined by particular MMSE cutoffs and increased risk of mortality [8][9][10][11][12][13][14][15][16]. To our knowledge, however, the associations between the entire range of MMSE scores, MMSE domains, and all-cause mortality are not well clear.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Campos et al 6 provide important detail that higher mortality is associated with cognitive impairment in community-dwelling older adults from a middleincome country. In this interesting and relevant study, a branch of the Bambuí Cohort Study of Aging, 7 1,281 older adults from a small rural town in southeastern Brazil were followed for 13.3 years.…”
mentioning
confidence: 98%